Antihyperglycemic and Antioxidant Activity of Nanoemulsion Extracts of M. affine D. Don Leaves in Alloxan-Induced Rat - Safrida Safrida; Khairil Khairil; Fani Fardinita (Journal of Tropical Biodiversity and Biotechnology, 2020)
This study determined the antihyperglycemic and antioxidant activity of nanoemulsion extracts of M. affine leaves in alloxan-induced rats. This research used 24 male Wistar rats around three months old which grouped as normal (untreated), negative control (treated with carboxymethyl cellulose sodium/Na-CMC,), positive control (treated with glibenclamide), and various concentration (30, 60, and 90%) of nanoemulsion extract of M. affine leaves groups. The extract of M. affine leaves had an antioxidant activity with IC50 5.30 ppm, categorized as a very strong antioxidant. Furthermore, the administration of this extract decreased glucose levels in antihyperglycemic rats.  We concluded that M. affine leaves extract potential as antioxidants and be developed as an ingredient for diabetic drugs.